Effectiveness of Emergency Department Patient Services in Terms of Nurse Competence, Team Coordination, and Work Motivation At Graha Juanda Hospital - Feby Wulansari; Wahyuni Dian Purwati; Rokiah Kusumapradja (International Forum of Researchers and Lecturers, 2025)
The Emergency Department (ED) plays a pivotal role as the frontline of hospital services, requiring rapid and accurate responses to ensure patient safety and optimal care outcomes. This study aims to analyze the influence of nurse competence and inter-team coordination on the effectiveness of patient transfers from ED to inpatient units, with nurse work motivation as a mediating variable. A quantitative approach was employed with hypothesis testing using path analysis (Structural Equation Modeling - SEM). The study was conducted at Graha Juanda Hospital, Bekasi, involving a sample of 55 nurses selected through total sampling from both the ED and inpatient departments. Primary data were collected through structured questionnaires, and data analysis was performed using SPSS 26. The results demonstrate that nurse competence and team coordination significantly affect service effectiveness, both directly and indirectly through work motivation. Specifically, high levels of nurse competence enhance the ability to assess, monitor, and manage patients efficiently, while effective team coordination fosters a collaborative environment that streamlines patient care transitions. However, work motivation plays a crucial role in mediating these relationships. The findings also indicate that low work motivation—linked to factors such as limited professional development opportunities, high workloads, and lack of recognition—contributes to delays in transferring patients to inpatient care, with the average Length of Stay (LOS) exceeding six hours. The study concludes that improving nurse competence, strengthening inter-team coordination, and enhancing nurse motivation are critical strategies to improve the quality and timeliness of emergency services. By offering continuous professional development, balancing workloads, and creating an environment where nurses feel valued, hospitals can significantly reduce delays in patient transfers. This integrated internal performance approach is vital for reducing LOS in the ED, ensuring timely care, and enhancing patient satisfaction. Furthermore, fostering a positive work environment that prioritizes both individual nurse growth and team collaboration is essential for sustaining high-quality emergency services and seamless, patient-centered care transitions.